2008
DOI: 10.1111/j.1742-4658.2008.06698.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of squamous cell carcinoma antigen‐1 in liver enhances the uptake of hepatitis B virus envelope‐derived bio‐nanocapsules in transgenic rats

Abstract: Hepatitis B virus (HBV) specifically infects the liver of humans and higher primates. The hepatophilic tropism of HBV is mainly determined by the function of the HBV envelope protein (also called HBV surface antigen; HBsAg), which consists of three proteins encoded by a single env gene: large (L; pre-S1 + pre-S2 + S regions), middle (M; pre-S2 + S regions) and small (S; only S region). In particular, the pre-S1 (21-47, subtype adr) region of the L protein has been revealed to play a crucial role in human liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…HSPG is abundantly expressed in the extracellular matrix of various tissues, which could interact with AGL of S region[ 8 , 11 ]. The binding of BNC to human hepatic cells[ 32 ] was efficiently suppressed by heparin[ 38 ]. Since the membrane topology of BNC is similar with HBV, HSPG might act as a low-affinity receptor for BNC.…”
Section: Bnc As a Model Of Hbvmentioning
confidence: 99%
“…HSPG is abundantly expressed in the extracellular matrix of various tissues, which could interact with AGL of S region[ 8 , 11 ]. The binding of BNC to human hepatic cells[ 32 ] was efficiently suppressed by heparin[ 38 ]. Since the membrane topology of BNC is similar with HBV, HSPG might act as a low-affinity receptor for BNC.…”
Section: Bnc As a Model Of Hbvmentioning
confidence: 99%
“…Experiments performed with the CysPreS1 peptide did not reveal any interaction (see the Supporting Information). Such an outcome was likely the result of the low molecular weight of the peptide, which reduced the amplitude of the instrument response, and of the possible low affinity of the peptide for SB3 at the concentration interval explored. , However, 1 -AuNPs revealed a quite-strong binding (Figure ). Association and dissociation profiles were rather complex and could be fitted only with a kinetic model, which includes two different binding modes of the nanoparticles to SB3 (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This protein is frequently up-regulated in several malignancies of epithelial origin and of the liver. Indeed, it is undetectable in normal hepatocytes, but it is overexpressed in hepatocellular carcinoma (HCC) and in hepatoblastoma. A few years ago, some researchers have demonstrated that SB3 is also a target of the hepatitis B virus (HBV), and a key recognition element is the PreS1(21–47) peptide, which is a fragment of one of the proteins composing the viral envelope. Other target proteins have been suggested for the HBV capsid, particularly for the PreS1 region.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of lipids to bionanocapsules produced a bionanocapsule-liposomal complex, which had greater stability when compared with HBV bionanocapsules [169]. Liposome-bionanocapsule complexes are produced at sizes less than 200 nm, preventing the removal of the formulation by macrophages in the bloodstream [163,170].…”
Section: Bionanocapsule-liposome Complexesmentioning
confidence: 99%